Determinant of Non-Performing Financing in Indonesian Islamic Commercial Banks in time of Covid-19 Pandemic - Fitria Idham Chalid; Firsty Izzata Bella (IAIN Syekh Nurjati Cirebon, 2021)
This study intended to determine the influence of internal and external factors of Islamic banks on the Non-Performing Financing (NPF) ratio during the global financial crisis effect Covid-19. This research by utilizing quarterly data on the panel data method with 11 Islamic Commercial Banks (IBs) in the 2019Q1-2020Q4 period sourced from financial report of each bank and the Central Statistics Agency (BPS). The results indicate that all independent variables, namely the Financing to Deposit Ratio (FDR), Bank Size, and Economic Growth have a significant negative effect on NPF, except for the Capital Adequacy Ratio (CAR). This can be inferred that the credit restructuring policy enacted by the Indonesian government has been effectively decreasing the ratio of NPF in banks, especially for IBs in Indonesia during the pandemic of Covid-19